2023
DOI: 10.1021/acs.est.3c04757
|View full text |Cite
|
Sign up to set email alerts
|

Isotopic Evidence for Microbial Nitrogen Cycling in a Glacier Interior of High-Mountain Asia

Shohei Hattori,
Zhongqin Li,
Naohiro Yoshida
et al.

Abstract: Glaciers are now acknowledged as an important biome globally, but biological processes in the interior of the glacier (englacial) are thought to be slow and to play only a minor role in biogeochemical cycles. In this study, we demonstrate extensive, microbially driven englacial nitrogen cycling in an Asian glacier using the stable isotopes (δ 15 N, δ 18 O, and Δ 17 O values) of nitrate. Apparent decreases in Δ 17 O values of nitrate in an 8 m shallow firn core from the accumulation area indicate that nitrifier… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 82 publications
0
1
0
Order By: Relevance
“…An investigation of the NO 3 – isotopic values of ice cores from Urumqi Glacier No. 1 revealed that N deposited in glaciers could undergo in-suit nitrification and microbial consumption . Glacial lakes and glacier-fed rivers in proglacial environments serve as major recipients and distributors of glacier-derived NO 3 – and nitrification-related microorganisms. ,, The highly hydrological connectivity and unique topography of high-mountain glacier regions facilitate the rapid transport of glacier-derived NO 3 – .…”
Section: Introductionmentioning
confidence: 99%
“…An investigation of the NO 3 – isotopic values of ice cores from Urumqi Glacier No. 1 revealed that N deposited in glaciers could undergo in-suit nitrification and microbial consumption . Glacial lakes and glacier-fed rivers in proglacial environments serve as major recipients and distributors of glacier-derived NO 3 – and nitrification-related microorganisms. ,, The highly hydrological connectivity and unique topography of high-mountain glacier regions facilitate the rapid transport of glacier-derived NO 3 – .…”
Section: Introductionmentioning
confidence: 99%